2007
DOI: 10.1051/vetres:2006048
|View full text |Cite
|
Sign up to set email alerts
|

Immunological and gene expression responses to aSalmonellainfection in the chicken intestine

Abstract: -Besides infection in humans, Salmonella enteritidis can also cause serious illness in young chickens. However, the genetic and immunological parameters important for the disease in chickens are not well characterized. In this study, processes in the chicken intestine in response to a Salmonella infection were investigated in two different chicken lines. One-day-old chickens were orally infected with Salmonella. T-cell subpopulations, phagocytic properties of intestinal mononuclear cells and RNA expression lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 26 publications
(34 reference statements)
3
20
0
2
Order By: Relevance
“…Outros estudos avaliaram a interação dessas células em agregados linfoides intestinais após infecção oral com Salmonella em aves jovens (Sasai et al 2000, Berndt et al 2007, Hemert et al 2007. As células T CD8+ desempenham um importante papel no combate das infecções primárias por salmonelas, assim como a resposta por IgA e leucócitos polimorfonucleados (Berndt & Methener 2001).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Outros estudos avaliaram a interação dessas células em agregados linfoides intestinais após infecção oral com Salmonella em aves jovens (Sasai et al 2000, Berndt et al 2007, Hemert et al 2007. As células T CD8+ desempenham um importante papel no combate das infecções primárias por salmonelas, assim como a resposta por IgA e leucócitos polimorfonucleados (Berndt & Methener 2001).…”
Section: Discussionunclassified
“…Em contrapartida, Hemert et al (2007) mostraram diminuição na contagem destas células no jejuno ao primeiro e ao quinto dia pós-inoculação oral de 0,2 ml de 10 5 UFC/ml de Salmonella Enteritidis quando comparado com o controle negativo.…”
Section: Discussionunclassified
“…For instance, van Hemert et al identified differential expression of genes by microarray experiments in intestinal tissue sampled from chicks infected with S. Enteritidis and uninfected individuals [810]. Similarly, Schokker et al identified 20 key hub genes by analyzing a time series of microarray data of intestinal tissues collected at different time points after day-old chicks were infected with S. Enteritidis [11].…”
Section: Introductionmentioning
confidence: 99%
“…Associations have also been reported with a variety of candidate genes (Kramer et al, 2003;Malek et al, 2004), which include MHC polymorphisms and NRAMP Lamont et al, 2002;Liu et al, 2003). Gene expression differences in response to the bacteria have been found (Van Hemert et al, 2006 and, as well as significant changes in cytokine expression (Kaiser et al, 2006) and in common processes in the chicken intestine (Van Hemert et al, 2007). Clearly, host genetic variations to Salmonella infections in poultry are being studied extensively and, given the developed state of chicken genomic tools, Salmonella is a high-priority candidate for OG studies.…”
Section: Davies Genini Bishop and Giufframentioning
confidence: 99%